SnCN2: A Carbodiimide with an Innovative Approach for Energy Storage Systems and Phosphors in Modern LED Technology. Issue 22 (6th October 2020) - Braun, Cordula; Mereacre, Liuda; Hua, Weibo; Stürzer, Tobias; Ponomarev, Ilia; Kroll, Peter; Slabon, Adam; Chen, Zheng; Damour, Yann; Rocquefelte, Xavier; Halet, Jean‐François; Indris, Sylvio
Abstract: The carbodiimide SnCN2 was prepared at low temperatures (400 °C–550 °C) by using a patented urea precursor route. The crystal structure of SnCN2 was determined from single‐crystal data in space group C 2 /c (no. 15) with a =9.1547(5), b =5.0209(3), c =6.0903(3) Å, β =117.672(3), V =247.92 Å 3 and Z =4. As carbodiimide compounds display remarkably high thermal and chemical resistivity, SnCN2 has been doped with Eu and Tb to test it for its application in future phosphor‐converted LEDs. This doping of SnCN2 proved that a color tuning of the carbodiimide host with different activator ions and the combination of the latter ones is possible. Additionally, as the search for novel high‐performing electrode materials is essential for current battery technologies, this carbodiimide has been investigated concerning its use in lithium‐ion batteries. To further elucidate its application possibilities in materials science, several characterization steps and physical measurements (XRD, in situ XANES, Sn Mössbauer spectroscopy, thermal expansion, IR spectroscopy, Mott‐Schottky analysis) were carried out. The electronic structure of the n ‐type semiconductor SnCN2 has been probed using X‐ray absorption spectroscopy and density functional theory (DFT) computations. Abstract : LED the way : The carbodiimide SnCN2 is prepared at low temperatures by using a urea precursor route. Tuning of the materials properties of SnCN2 + by cation doping (Eu 3+, Tb 3+, transition metals) led to comprehensive luminescence studies and battery investigations. This confirms the perspectives of SnCN2 as a promising compound for future phosphor‐converted LEDs and novel high‐performing electrode materials for Li‐ion batteries.